Characterization of myocardial hypertrophy by DNA content, PCNA expression and apoptotic index - Matturri, Luigi (2002)
Background: At present little is known about the biological basis of cellular alterations in myocardial hypertrophy. The present study aims to analyze proliferating cell nuclear antigen (PCNA) expression, DNA content and apoptosis, in several types of myocardial hypertrophy in order to define the biological characteristics of this process. Methods: The biological parameters were investigated in normal hearts (n=4) and in 21 cases of left ventricular myocardial hypertrophy related to pressure overload (n=7), post-infarction remodeling (n=8) and hypertrophic cardiomyopathy (HCM) (n=8). Results: The analyzed biomarkers were similar in hypertension and in remodeling, with a very high apoptotic index (mean values: 8.1 and 8.5%, respectively), a low PCNA positivity (mean values: 1.8 and 1.6%) and a prevalent diploid DNA content (DNA index: 1.2). Conversely, HCM showed a high mean PCNA index (21.2%) associated with a prevalence of hyperdiploid myocytes (DNA index: 1.8) and a low number of apoptotic cells (mean value: 1.7%). Conclusions: There are significant biological differences between hypertrophy in HCM and that related to arterial hypertension and post-infarction remodeling. Therefore, the combined evaluation of DNA content, PCNA and apoptotic indices could provide a powerful diagnostic tool in doubtful cases of myocardial primary or secondary hypertrophy and open new avenues in the clinical treatment of these entities.